Class switching toward IgG4 six months after primary mRNA-based COVID-19 vaccination in kidney patients - Sophie C. Frölke; Kenney G. Amirkhan; Nelly van der Bom-Baylon; Marit van Gils; Mathieu Claireaux; Suzanne E. Geerlings; Rory D. de Vries; Jan-Stephan F. Sanders; Luuk B. Hilbrands; Dimitri A. Diavatopoulos; A. Lianne Messchendorp; Michiel C. van Aalderen; et al. (PLoS ONE, 2026)
Background Class switching toward spike (S)-binding IgG4 antibodies after mRNA-based COVID-19 vaccination has been observed, an antibody subclass with strong neutralizing but limited effector activity. While this has been reported in healthy individuals, subclass dynamics in immunocompromised kidney patients are unclear. We assessed IgG subclass patterns and S-specific B-cell phenotypes up to 6 months after a two-dose mRNA-1273 vaccination schedule in kidney transplant recipients (KTRs), dialysis patients, and patients with chronic kidney disease (CKD). Methods In this exploratory study, KTRs (n = 11), dialysis patients (n = 5), CKD stage G4–5 patients (eGFR < 30 ml/min/1.73m2, n = 5), and controls without known kidney disease (eGFR > 45 ml/min/1.73m2, n = 8) received two mRNA-1273 doses 28 days apart. Blood was collected pre-vaccination (V1), and at 28 days (V3) and 6 months (V4) after the second dose. S1-specific IgG antibodies were measured by a validated fluorescent bead-based multiplex-immunoassay, and participants seronegative at V1 and seropositive at V3 were included. B cells were phenotyped by flow cytometry. Results Five of 11 KTRs had no detectable S-binding B cells, whereas all other groups mounted responses. Across responders, the frequency of S-binding B cells increased from V1 (median 0.08%) to 0.49% at V3 and to 0.84% at V4 (both p < 0.0001). S-binding B cells mainly comprised IgG⁺ plasmablasts. The IgG4:IgG1 log-ratio increased significantly from V3 to V4 (p < 0.001), indicating a relative shift toward IgG4; absolute frequencies were comparable across the groups. Conclusions Approximately half of KTRs lacked detectable S-binding B cells after two mRNA-1273 doses, despite antibody formation. Among responders, S-binding B cells persisted up to 6 months after vaccination with a relative shift toward IgG4, a pattern also observed in dialysis patients, CKD patients and controls. The clinical significance of this subclass skewing requires confirmation in larger cohorts with functional antibody readouts.